Pendapat Guru terhadap Implementasi Kurikulum 2013 di SMK Negeri 5 Padang - Rendi Warwan (Universitas Negeri Padang, 2019)
This study aims to determine the teacher's opinion on the implementation of the 2013 curriculum at SMK Negeri 5 Padang majoring in Electrical Power Installation Engineering and describing the obstacles in its implementation. This research is a qualitative descriptive research which studies understand the phenomena about what is experienced by the research subjects. This study uses structured interview instruments. The research data are in the form of descriptions and analysis, so that answers are obtained from the problems studied. The subject of this study was teachers at SMK 5 Padang, Electric Power Installation Engineering Department. The results of this study indicate that: (1) the teacher's opinion is positive because it welcomes the implementation of the 2013 curriculum, supported by sufficient training, so that teachers can apply the concepts of learning in accordance with the 2013 curriculum such as the preparation of lesson plans, authentic assessment and scientific approaches; (2) teacher constraints in the form of technical problems, but this can be overcome by developing themselves and their knowledge.